Use intention of automated self-service services in mobile telecom - Costa, Tito Mendes da; Ferreira, Jorge Brantes; Freitas, Angilberto Sabino de; Rodrigues, Juliana Werneck; Ramos, Fernanda Leão (Revista de Administração da UFSM, 2019)
The aim of this study is to propose a model to evaluate consumers’ intention of adopting a new type customer service technology, self-service customer services (SSCS), analyzing the effects that consumers’ cognitive and affective perceptions about technology along with their communication with peers in social media have on their intention to adopt services of this nature. An online questionnaire was made available over the Internet to a base of 830,000 customers of a large mobile telecom carrier, with 5,262 valid questionnaires being obtained in response. Through structural equation modeling, the assumptions of the model were tested and the results show evidence of the influence of cognitive, emotional and social aspects on the consumer intention to adopt self-service customer service technologies.